Practical Significance of Surface Ion Effects in Solids (Eurasian Journal of Humanities and Social Sciences, 2021)
Adsorption of an atom or molecule on the surface of an inflamed solid body or diffusion out of the solid body and the establishment of thermodynamic and charge balance between the adsorbed particle and the solid body, and thermodesorption of particles from the surface of the solid body. During thermodesorption, the charge state of the particles is determined. The charge state of a desorbed particle is determined by the isothermal electron exchange between the particle and the solid. In this paper, the main condition is that the occurrence of the phenomenon without changing the thermoemission properties of the surface of the adsorbed particles falling on the surface.